The effect of attitude, subjective norm, perceived behavioral control and gender on whistleblowing intention - Larasati, Meita; Nugroho, Arif Widodo; Rahayu, Dewi Pudji; Susanti, Susi; Cahyani, Meti Regita (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study aims to investigate the impact of Attitudes, Subjective Norms, Perceived Behavioral Control, and Gender on Whistleblowing Intentions among auditors.Design/Methodology/Approach: The research uses Attitudes, Subjective Norms, Perceived Behavioral Control, and Gender as independent variables, with Whistleblowing Intention as the dependent variable. The sample consists of 202 auditors working at Public Accounting Firms (PAF) in East and South Jakarta. Data were analyzed using SmartPLS version 4.0.93.Research findings: The results show that Attitudes, Subjective Norms, and Perceived Behavioral Control positively influence whistleblowing intentions. However, Gender does not have a significant effect. Collectively, the variables influence whistleblowing intentions, with an adjusted R-square of 32.10%.Theoretical Contribution/Originality: This study expands the limited research on whistleblowing in Indonesia, particularly among external auditors, and provides empirical evidence concerning behavioral factors influencing whistleblowing intentions.Practitioner/Policy implication: The findings offer guidance for organizations in developing effective training, internal policies, and reporting systems to strengthen whistleblowing culture and support fraud prevention.Research limitation/Implication: Whistleblowing intentions are explained by only 32.10% of the tested variables, indicating that 67.90% is influenced by other factors such as religiosity, professionalism, and perceived good governance. Future research should include additional variables and larger samples to capture broader behavioral dynamics.